EFEKTIVITAS PENGELOLAAN DAN PENGENDALIAN PIUTANG DALAM UPAYA MEMINIMALISIR PIUTANG TAK TERTAGIH PADA PT. ADP - Mega Kusuma Prakoso; Wasti Reviandani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to evaluate and assess how good PT. ADP manages and controls its receivables. A qualitative approach is applied in descriptive research methodologies. Analytical techniques are only limited to examining the control of receivables with elements of internal control and analyzing the management of receivables with financial ratios related to receivables. Both primary and secondary data are consulted for gathering data. Utilize observation, interviews, and documentation as a data collection strategy. The results showed that the management and control of PT ADP's receivables was still insufficient to reduce the amount of uncollectible receivables caused by Indonesia's difficult economic situation when COVID-19 was widespread and there was a dearth of a clear separation of duties, which had an impact on the receivables collection process.